2021
DOI: 10.1007/s11948-021-00294-w
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement: Unanswered Questions About Human Psychology and Social Behavior

Abstract: Stimulant drugs, transcranial magnetic stimulation, brain-computer interfaces, and even genetic modifications are all discussed as forms of potential cognitive enhancement. Cognitive enhancement can be conceived as a benefit-seeking strategy used by healthy individuals to enhance cognitive abilities such as learning, memory, attention, or vigilance. This phenomenon is hotly debated in the public, professional, and scientific literature. Many of the statements favoring cognitive enhancement (e.g., related to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 86 publications
0
28
0
Order By: Relevance
“…The understanding of CEs and their potential advantages are critical in deciding their utilization among users. It is observed that the individuals who thought CE use is morally and socially acceptable are more probable to utilize CEs (Racine et al, 2021). When respondents were inquired if they would use a hypothetical prescription-only CE that has been demonstrated to be effective, has been approved by regulatory authorities, and has no severe adverse effects, professionals' hypothetical readiness to utilize CEs (19.7%) was greater than the prevalence observed by students (Ram et al, 2021), although the motivations for use are the same for both professionals and students.…”
Section: Discussionmentioning
confidence: 99%
“…The understanding of CEs and their potential advantages are critical in deciding their utilization among users. It is observed that the individuals who thought CE use is morally and socially acceptable are more probable to utilize CEs (Racine et al, 2021). When respondents were inquired if they would use a hypothetical prescription-only CE that has been demonstrated to be effective, has been approved by regulatory authorities, and has no severe adverse effects, professionals' hypothetical readiness to utilize CEs (19.7%) was greater than the prevalence observed by students (Ram et al, 2021), although the motivations for use are the same for both professionals and students.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond scholarly interest in the subject, several projects in foresight, technology assessment, and bioethics have addressed the social, legal and ethical aspects of neuroenhancement [e.g., 4 , 5 , 6 , 7 , 8 , 9 ]. The majority of discussions around neuroenhancement have tended to focus upon the distinction between therapeutic and enhancing interventions, alongside questions concerning the proper scope of medicine, while some have linked this to broader questions relating to the societal implications of embracing such technology in sports and in the workplace [e.g., 10 , 11 , 12 ]. Interest has also emerged in studying the potential of neuroenhancement in and for specific groups, such as medical doctors, scientists, airline pilots or military personnel whose professional duties can greatly impact upon the welfare of others [ 13 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also concern given the possible negative health consequences arising from such drug misuse, which can include addiction. Moreover, such use may result in drug-related crimes or pressure on non-users to take drugs to compete with drug users and increase performance standards [32][33][34]. Therefore, investigating the drivers of such drug misuse is important for public health interventions, occupational health, and policy making.…”
Section: Introductionmentioning
confidence: 99%